Second harmonic scattering from mass characterized 2D graphene oxide sheets. Issue 27 (5th March 2020) - Russier-Antoine, Isabelle; Fakhouri, Hussein; Basu, Srestha; Bertorelle, Franck; Dugourd, Philippe; Brevet, Pierre-François; Velayudhan, Prajitha; Thomas, Sabu; Kalarikkal, Nandakumar; Antoine, Rodolphe
Abstract : We report the second harmonic scattering and its orientation-averaged hyperpolarizability from mass characterized 2D graphene oxide sheets dispersed in an aqueous suspension. Abstract : In this communication, we report the second harmonic scattering from mass characterized 2D graphene oxide sheets dispersed in an aqueous suspension, in the femtosecond regime at 800 nm laser excitation. Charge-detection mass-spectrometry, performing at the single sheet level, allows for an exhaustive molar mass distribution and thus concentration for these 2D nanomaterials samples. The orientation-averaged hyperpolarizability value is (1.36 ± 0.15) × 10 −25 esu as determined by the concentration-dependent harmonic scattering signal. In addition, the multi-photon excited fluorescence spectrum is characterized by a broad band in the visible range between 350 and 700 nm centered at about 500 nm.